Searching the New Labyrinth: the Echoes of Mercutio’s Banter in Paul’s Cross Churchyard - Dabbs, T (2013)
This talk will examine one highly referential speech by Mercutio in Shakespeare's Romeo and Juliet in order to bring forward certain heretofore hidden elements within the physical architecture and also the architecture of consciousness at St Paul's during the 1590s. It will focus on the bookselling district of Paul’s Cross Churchyard on the northeast side of the cathedral. To do this EEBO-TCP and other digital resources in various degrees of development will be assessed along with static, hard copy research. In Act II, scene IV, of Romeo and Juliet, Mercutio sardonically references six romantic heroines, who, he asserts, Romeo wishes to place his own love interest above.1 In each case, an EEBO-TCP search shows that the names of the mythological women Mercutio mentions had a comeuppance in then printed works during the 1590s. The title pages of these works and other records indicate that these texts were available from bookshops in Paul’s Cross Churchyard in the years subsequent to Romeo and Juliet. Instead of just being bawdy banter, Mercutio’s speech points to the print marketplace in the churchyard and shows how a Shakespearean play echoed stories and fashions that were popular, not in Verona, but in the City of London. Recently, the team at the Virtual Paul’s Cross Project has reconstructed much of St Paul’s cathedral during the early modern period. From this reconstruction and also the search capabilities of EEBO-TCP, we can now identify relationships between this area and the Shakespearean stage with far more precision than before. We still do not know precisely how books were retailed, how long they were held in stock, or how popular they actually were. Also certain significant full texts may not be available yet in a TCP search. These pitfalls noted, this talk will abide by the thesis that digital resources can bring us much closer to an understanding of a lost, physical world and also to human consciousness during the early modern period.